TMEM16F and dynamins control expansive plasma membrane reservoirs - Christine Deisl (Nature Portfolio, 2021)
Cells locally expand and retract their surface in response to environmental factors such as changes in membrane tension. Here the authors show the membrane adapter, dynamin2, locally constricts surface membrane to form an isolated but contiguous membrane reservoir that can open upon phospholipid scrambling via TMEM16F.